Biopetrol production from oil waste - Syaiful Nizam, Hassan (2008)
Biopetrol is defined as fuel which has the same characteristics with commercial petrol in terms of its molecular formula. The objective of this study is to find the concentration of biopetrol (isooctane) from fatty acids in palm oil waste, which are palmitic and oleic acids. Thermal cracking process is used to synthesize isooctane from palmitic and oleic acids. Heat is supplied at palmitic acid's melting point within a range of 63°C - 64 °C, to melt and liquefy the solid palmitic acid, whereas oleic acid is naturally in liquid form, so oleic acid is directly heated. The heating process for both acids is continuously performed until achieving isooctane's boiling point of 98 °C to form new arrangements of carbon compounds including isooctane. After the continuous heating process is completed, the samples from both fatty acids' distillates were collected at various temperatures, which are at 200°C, 300°C, 330°C and 350°C respectively. The desired isooctane obtained is around 0.0455% - 0.0743% in the distilled palmitic acid; and around 0.07793% - 0.39731% in the distilled oleic acid, with the presence of hexane as dilution solvent. After applying back calculation to obtain actual isooctane concentrations in both distillates with comparison to the pure isooctane, the highest concentration of the desired isooctane in palmitic acid distillate is 2.92% at temperature 350 °C, and in oleic acid distillate is 3.084% at temperature 280 °C. These resulting - concentrations can be increased and improved by using-catalytic cracking method.